Estimación del carbono almacenado en necromasa y suelo en la zona alta del cerro huicotango perteneciente a la comuna Tasinteo Mantugtuza del cantón Píllaro en el periodo diciembre 2021 – febrero 2022 - Pilataxi Diaz, Deisy Beatriz (2022)
The actual research had as aim to estimate the carbon content into soil and necromass in the Cerro Huicotango upper area belonging to the Tasinteo Mantugtuza Commune. For estimating the carbon content, the research was divided into three phases: field phase, laboratory phase and data analysis phase. It was set three permanent plots based on three different systems: agricultural plot, pasture plot and forest plot. It was got 36 soil samples at three different depths (0-30 cm), from the three set plots, what were suppressed to the process calcination or ignition (LOI) at a 360ºC temperature for 24h. For the carbon in necromass estimation, it was got different plant species 36 samples, what were selected, by means simple random sampling, samples, whose were dried into an oven at 120ºC for 24h to get the dry weight and perform the respective calculations. As a research result, it was got the following data: the average carbon storage into the soil is 69.78 tC/ha, being the forest plot, which presents the highest carbon content; with an 85.47 tC/ha average, while for the carbon content into necromass, the average value is 0.0022 tC/ha. With the made research, it can conclude, what the soil stores more than carbon 99%, while necromass does not store, even 1%, this is due to the OM and CO high concentrations, whose have the soil, turning it the largest drain of carbon, while necromass stores few C amounts, due to its rapid degradation and low plant density.